‘“Les années noires avaient été grises”: A Metaethical Analysis of Pierre Assouline’s Appropriation of Primo Levi’s “Grey Zone”’ - Helena Duffy (Pennsylvania University Press, 2022)
In his debut novel, La Cliente, which focuses on the relatively unexplored phenomenon of denunciation during World War II, Pierre Assouline explicitly applies Levi’s notion of “grey zone” to the French context by advancing a theory that the dark years — “les années noires” — were in fact not blackbut grey. He thus foregrounds the ambiguity of a period which is customarily understood in Manichean terms, the French being divided in popular consciousness into vile collaborators and heroic resisters. This article explores the ethics of Assouline’s appropriation of the notion of “grey zone,” which originally designated those forced into collusion with the Nazis by the horrific circumstances of the Final Solution, and who therefore, in Levi’s mind, must not be judged. As well as discussing the novelist’s use of Levi’s concept in relation to a French informer responsible for the death of a Jewish family, or his use of the figure of the mirror to invert the roles of victim and victimizer, the article extends the use of the term “grey zone” to the generic hybridity of La Cliente, which self-consciously straddles history and literary invention in order to convey the complexities of “les années grises.” Ultimately, the article argues that by mixing fact and fiction in order to create a character who is simultaneously the agent of Jewish deaths and victim of, first, blackmail by the French police, and then misguided épuration, Assouline risks manipulating his readers into suspending their moral judgment of informers. In other words, the novelist places collaborators in the same “ill-defined area of ambiguity and compromise […] born out of political coercion” where Levi situates the Jews who, detained in ghettos and concentration camps, faced what Lawrence Langer has called “choiceless choices.”